Erratum: YANG, XIUSHUAI & LIU, ZHIQI (2010) Notes on the genus Eumantispa Okamoto, 1910 from mainland of China (Neuroptera, Mantispidae). Zootaxa, 2669, 57–68. - Yang, Xiushuai; Liu, Zhiqi (Zootaxa, 2011)
(Erratum)